2011
DOI: 10.1111/j.1399-3062.2011.00661.x
|View full text |Cite
|
Sign up to set email alerts
|

Low incidence of invasive aspergillosis in allogeneic stem cell transplant recipients receiving amphotericin B inhalation prophylaxis

Abstract: In this retrospective study we evaluated the impact of amphotericin B (AmB) deoxycholate inhalation prophylaxis on invasive aspergillosis (IA) in 611 allogeneic stem cell transplant (alloSCT) recipients and their tolerance of the inhalations. The inhalations were not used in 1996-2000 (Period I). In 2001-2005 (Period II) all patients with acute graft-versus-host disease treated with high-dose methylprednisolone used the inhalation prophylaxis with a dose of 25 mg daily. No systemic antifungal prophylaxis was r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…Since the GITMO Consensus Conference published in 2009, only few studies on PAP in the allo-HSCT population have been published [42][43][44][45][46][47][48][49][50][51], and only 2 of them were prospective, randomized, multicenter trials [43,46] (Table 3).…”
Section: Primary Antifungal Prophylaxismentioning
confidence: 99%
See 1 more Smart Citation
“…Since the GITMO Consensus Conference published in 2009, only few studies on PAP in the allo-HSCT population have been published [42][43][44][45][46][47][48][49][50][51], and only 2 of them were prospective, randomized, multicenter trials [43,46] (Table 3).…”
Section: Primary Antifungal Prophylaxismentioning
confidence: 99%
“…There was no difference in incidence of proven/probable IFD (1.3% versus 2.1%) or survival to day 180 (81.9% versus 80.9%) for voriconazole and itraconazole, respectively. Nihtinen, 2012 [47] Retrospective, single center in patients with acute GVHD. AmB deoxycholate inhalation for a median duration of 84 days (n¼ 354) versus historical control (n ¼ 257).…”
Section: Primary Antifungal Prophylaxismentioning
confidence: 99%
“…The benefits of antifungal prophylaxis should outweigh the drug toxicities . A growing body of clinical evidence suggests that antifungal prophylaxis reduces fungal infection‐related mortality and transplant‐related mortality in patients undergoing HSCT, thus improving survival .…”
Section: Discussionmentioning
confidence: 99%
“…Several trials have examined the use of amphotericin B for prophylaxis of IFD. [48][49][50][51][52][53] Smaller studies have demonstrated that amphotericin is safe and effective in preventing IFD in HCT patients. 48,49 However, trials comparing amphotericin to posaconazole have demonstrated higher rates of adverse effects with amphotericin, such as nephrotoxicity.…”
Section: Options For Antifungal Prophylaxismentioning
confidence: 99%
“…50,53 Retrospective trials using aerosolized amphotericin B have shown this to be a safe and effective strategy for fungal prophylaxis in HCT, but there are no published prospective trials examining its efficacy. 51,52 Voriconazole has been studied extensively as a prophylactic agent in the HCT setting. 33,[54][55][56][57][58] Adverse effects of voriconazole include hepatotoxicity, prolongation of the QTc interval and visual disturbances.…”
Section: Options For Antifungal Prophylaxismentioning
confidence: 99%